(untitled) (Academia Science Repository, 2023)
It is known that tuberculosis is currently one of the most common diseases of social importance in the world, and it is a serious somatic disease with certain mental disorders. Hypochondriac disorders play an important role in the psychological course of tuberculosis. The feeling of alienation and isolation leads to the breakdown of interpersonal relationships, accompanied by schizoid thinking and reasoning. Disturbances of the psychological state are typical for both patients with tuberculosis diagnosed for the first time, and for men and women who have been ill for a long time. It follows from the correlations that replacing the patient’s usual coping strategies (distancing, avoiding) with flexible strategies (seeking social support, taking responsibility) can positively change the patient’s attitude to the disease. This, in turn, leads to greater efficiency in the fight for its treatment prospects and health restoration.Almost all patients with urinary tract tuberculosis who participated in corrective and developmental work improved their flexibility. An important result is that medical workers have shown positive changes in the behavior of patients with urinary tract tuberculosis, their willingness to show kindness and, most importantly, their willingness to cooperate in the fight against the disease.